The Versatility of the Free Vastus Lateralis Muscle Flap: Orbital Reconstruction After Removal of Complex Vascular Malformation in a Pediatric Patient - Grussu, Francesca; Santecchia, Luigino; Urbani, Urbano; Spuntarelli, Giorgio; Rollo, Massimo; El Hachem, May; Romanzo, Antonino; Zama, Mario (Frontiers in Pediatrics, 2021)
INTRODUCTION:Pediatric vascular orbital lesions represent a demanding therapeutic challenge and,in severe cases,orbital enucleation can be considered.Surgical management of enucleated orbital region in children represents a challenging procedure owing to the intrinsic relation between volume replacement and normal orbital growth.Many reconstructive options have been proposed and many donor sites have been utilized for this purpose but each one have demonstrated potential disadvantages.Despite its well-known versatility,no report of the vastus lateralis free flap in children requiring orbital reconstruction exists in literature.Herein we propose this surgical strategy as a valid option for the reconstruction of an extended orbital defect in a pediatric patient suffering from a mixed type of vascular malformation. MATERIAL AND METHODS:A patient was referred to our unit with an unclear medical history,presenting exorbitism and exophthalmos,proptosis of the eyeball,visus 4/10,limited ocular motility.We made clinical-instrumental investigations with a diagnosis of complex vascular malformation of the intraorbital and retrorbital space with bulb anterior dislocation and optic nerve involvement.We performed an emptying of the orbital content via transconjunctival and coronal incision with eyelid preservation.A free vastus lateralis muscle flap was used for reconstruction,filling the orbital cavity.An ocular conformator was then positioned.RESULTS:We report the result at twelve months, showing a good orbital rehabilitation with an adequate prosthetic cavity, a good recovery of volume and facial symmetry, guaranteeing balanced orbital and periorbital growth.There were no major or minor complications associated with the procedure.DISCUSSION:The reconstruction of the orbit remains a "surgical challenge" both in adults, whose goal is the restoration of volume, adequate symmetry and facial aesthetics, and children,in which correcting the asymmetry has the additional objective to balance orbital growth.Many reconstructive techniques have been proposed, including the use of free flaps.The versatility of the free vastus lateralis muscle flap is well known.It offers adequate amount of tissue with minimal morbidity to the donor site,provides a long pedicle,the possibility of simultaneous work in a double team,has a constant anatomy and a safe and rapid dissection.There are no descriptions of its use for pediatric orbital reconstructions.CONCLUSIONS:In our opinion the free vastus lateralis flap should be included as one of the best option for orbital pediatric reconstruction after enucleation.